Strategi Penjualan Online Usaha Ainul Online Shop Dalam Konsep Ekonomi Islam Menurut Abu Bakar Ash-Shiddiq - Muhammad Ibnu Rinaldi (CV Edujavare Publishing, 2023)
Sales are activities or businesses that sell products or services. In the sales process, the seller or supplier of goods and services transfers ownership of the goods to the buyer at a certain price. Sales can be done in various ways, including through direct sales and indirect sales or sales representatives. The people involved in selling are referred to as salespeople. Sales is also an activity that aims to find, influence and direct buyers so that buyers can match their needs with the products offered and reach mutually beneficial price agreements. The method used in this study is a qualitative method, with a case study research design to make it easier to draw conclusions on the research results. This study uses interview techniques with data sources derived from business interviews that I have, namely the sale of women's clothes such as robes, negligee, and other suits. I do online sales in accordance with the concept of Islamic economics. This is because the concept of online sales has been well implemented, where in the Islamic concept there is no prohibition on making a profit, as long as it does not burden the buyer and the agreement between the two.